Study of Element Abundance in Volcanic Rocks in the Beruang Kanan Region, Gunung Mas Regency, Central Kalimantan - Retno Anjarwati; Sutarto Sutarto; Dwi Fitri Yudiantoro; Arifudin Idrus (Pelopor Publikasi Akademika, 2024)
Soil elements, based on their abundance in the earth's crust and petrogenetic analysis aim to divide soil elements into several groups, namely major elements, trace elements and rare earth elements (REE). The research location is located in the Beruang Kanan area, Tumbang Miri District, Gunung Mas Regency, Central Kalimantan Province. The major elements and trace elements of the host rock were obtained from X-ray fluorescence (XRF) analysis and Plasma-Coupled Mass Spectrometry (ICP-MS) methods. Volcanic rocks from the Kanan Bear prospect The volcanic magmatic affinity in the study area is calc-alkaline this chemical characteristic is clearly reflected by the type of volcanic rock which is determined based on its chemical classification, which is generally igneous rock of the calc-alkaline magma series type so it is interpreted to originate from a convergent tectonic environment continental edge.